183 dagar eller sex månader? - Svensk beskattning av tjänsteresenärer med ett formellt respektive ekonomiskt arbetsgivarsynsätt i ett EU-rättsligt perspektiv - Huitfeldt,Fredrik (2020)
The Swedish government has proposed introducing the concept of economic employer in Swedish tax law. The changes are proposed to take effect on 1 January 2021 and entail that some individuals, whose income was previously tax exempt due to the so called 183-day rule, now will be subject to Swedish income tax. This applies to situations of hiring-out of labour. A hiring-out of labour situation occurs when an individual, employed by a foreign employer, carries out work as an integrated part of the business activities of a Swedish person. The Swedish person is then considered as the foreign individual’s economic employer resulting in the foreign individual being subject to Swedish income tax on income earned while working in Sweden, as if employed in Sweden. Due to transfer pricing rules on intra-group services, the new rules will in some cases apply to short-term business travellers that are limited tax residents in Sweden. In these cases, tax liability will arise for income earned during business trips to Sweden. Swedish unlimited tax residents working abroad can under some circumstances claim tax exemption in accordance with the so called six-month rule or one-year rule for income earned through their foreign employment relating to work carried out both abroad and in Sweden. As a result, short-term business travellers employed abroad but with unlimited tax residency in Sweden can claim tax exemption for income related to work in Sweden in situations where limited tax residents cannot. This thesis examines how tax residency status for short term business travellers affect their effective taxation in Sweden. The current legislation is analysed from an EU-regulatory perspective to determine if the rules comply with the free movement doctrine. Further, the effect on short term business travellers of an economic employer view is examined and the proposed legislation’s compliance with the free movement of labour is analysed. This thesis concludes that the current Swedish rules on tax exemption for short-term business travellers limits the free movement of labour within the EU in cases where limited tax residents cannot claim tax exemption while unlimited tax residents in a comparable situation can claim such exemption in accordance with the six-month rule or one-year rule and the double taxation on limited tax residents is not fully neutralized through the applicable tax treaty. It is further concluded in this thesis that an economic employer view will increase the number of cases where the free movement of labour is limited through discrepancies in tax exemption doctrines for short-term business travellers depending on their tax residency status.
Keywords: EU-rätt; EU law; skatterätt; tax law; ekonomisk arbetsgivare; economic employer